DINAMIKA POLITIK IDENTITAS MASYARAKAT MUSLIM BALI PADA PILGUB BALI TAHUN 2018 - I Gusti Made Arya Suta Witawan (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2018)
The condition of a multicultural society causes democracy in Indonesia to be inseparable from political identity. Not only in regions, political identity also occured in the capital city, where the impact of this also influences people's perceptions from outside the capital about how they should be involved in politics. One issue related to political identity that has recently emerged and spread in various regions is the prohibition for Muslims to choose non-Muslim leaders to become regional heads. But what about the election of the Governor of Bali in 2018 where the Muslim community becomes a minority group and politically does not have a gubernatorial candidate and vice-governor candidate from among them while now some circles of Muslim communities are aggressively promoting their political identity. This research shows that the political identity movement of Muslim communities in Bali is very dynamic especially in situations where they consider themselves to be a minority group. The Balinese Muslim community continues to provide support and even choose non-Muslim leaders as far as the political agenda of the existing governor and deputy governor candidate pairs does not contradict their political identity. By using a qualitative approach this research also shows that all candidate pairs carry out various political approaches to the Balinese Muslim community, which shows that now the Balinese Muslim community which is a minority group has a political bargaining position.Keywords: political identity, Bali Muslim Society, Governor Election